Compendium of Surface and Interface Analysis (Springer Singapore, 2018)
This book concisely illustrates the techniques of major surface analysis and their applications to a few key examples. Surfaces play crucial roles in various interfacial processes, and their electronic/geometric structures rule the physical/chemical properties. In the last several decades, various techniques for surface analysis have been developed in conjunction with advances in optics, electronics, and quantum beams. This book provides a useful resource for a wide range of scientists and engineers from students to professionals in understanding the main points of each technique, such as principles, capabilities and requirements, at a glance. It is a contemporary encyclopedia for selecting the appropriate method depending on the reader's purpose. .